Carbon dots from tryptophan doped glucose for peroxynitrite sensing - Simões, Eliana F. C. (2014)
Tryptophan doped carbon dots (Trp-CD) were microwave synthesized. The optimum conditions of synthesizing of the Trp-CD were established by response surface multivariate optimization methodologies and were the following: 2.5 g of glucose and 300 mg of tryptophan diluted in 15 mL of water exposed for 5 min to a microwave radiation of 700 W. Trp-CD have an average size of 20 nm, were fluorescent with a quantum yield of 12.4% and the presence of peroxynitrite anion (ONOO−) provokes quenching of the fluorescence. The evaluated analytical methodology for ONOO− detection shows a linear response range from 5 to 25 μM with a limit of detection of 1.5 μM and quantification of 4.9 μM. The capability of the ONOO− quantification was evaluated in standard solutions and in fortified serum samples.